Problems of IT startups’ development in Ukraine - Mrykhina, Oleksandra (Видавництво Львівської політехніки, 2013)
This article contains researched features of the formation and development of the IT startups in Ukraine; potential of the domestic Internet market from the standpoint of creating startups; problems and prospects of Ukrainian startups’ advancement in the transitional economics are analyzed and the main ways of stimulation of their development are proved. A special attention is paid to the article assessment of technology transfer of IT startups. The article includes a comparative analysis of the experience of existence IT startups all over the world and in Ukraine. The novelty of this article lies in justification and guidelines systematization to encourage local IT startups, as well as in the approaches to diagnose trends on the Internet market based on prediction.
Keywords: IT startups; technology transfer; Internet market; transitional economics